Selenium deficiency in inflammatory bowel disease: A comprehensive meta-analysis - Sishuo Liu; Tingting Lin; Wenguang Wang; Fangyuan Jing; Jinghao Sheng (Heliyon)
Background: Micronutrient deficiencies, particularly selenium, are common in Inflammatory Bowel Diseases and may influence disease progression and severity. Various studies have investigated blood selenium levels in patients with inflammatory bowel disease, but these studies have shown considerable heterogeneity and are generally limited by small sample sizes. Therefore, this study aims to clarify the selenium status in patients with inflammatory bowel disease compared to controls and to explore the potential of selenium supplementation as a therapeutic option. Method: A comprehensive search of online databases from January 1980 to December 2023 was conducted, focusing on studies related to selenium levels in patients with inflammatory bowel disease. The relationship between blood selenium concentrations in inflammatory bowel disease patients and controls was pooled using a random-effects model. Results: From the 1853 references screened, 20 studies were selected based on the inclusion criteria, involving 1792 inflammatory bowel disease patients (including both Crohn's disease and ulcerative colitis cases) and 1648 controls. The meta-analysis demonstrated that inflammatory bowel disease patients have significantly lower selenium levels compared to the control group. This trend was consistent across subgroups differentiated by study characteristics such as design, geographical location, selenium detection methods, types of samples analyzed, and age categories of participants, with particularly notable deficiencies observed in patients with Crohn's disease. The robustness of these findings was supported by sensitivity analysis, and tests for publication bias indicated no significant skewing of results. Conclusion: The analysis confirms that inflammatory bowel disease patients, especially those with Crohn's disease, have significantly lower levels of selenium compared to controls, suggesting that that selenium supplementation may serve as a valuable adjunct to the therapeutic regimen for managing inflammatory bowel disease, particularly in patients identified with selenium insufficiency.